2010
DOI: 10.1175/2010jas3463.1
|View full text |Cite
|
Sign up to set email alerts
|

Particle Growth and Drop Collection Efficiency of Warm Clouds as Inferred from Joint CloudSat and MODIS Observations

Abstract: This study describes an approach for combining CloudSat and Moderate Resolution Imaging Spectroradiometer (MODIS) satellite observations to investigate the microphysical processes of warm clouds on the global scale. MODIS column optical thickness is vertically distributed between the cloud top and cloud bottom according to adiabatic and condensational growth assumptions and used as a vertical coordinate system to analyze profiles of CloudSat-observed radar reflectivity. The reflectivity profiles thus rescaled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
156
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(166 citation statements)
references
References 25 publications
10
156
0
Order By: Relevance
“…Platnick (2000) showed that dτ has some dependence on viewing geometry and so the consideration of a wider range of view and solar zenith angles should ideally be made. The modelling of the idealised clouds and the correction rests on the assumption that r e increases monotonically with height within the cloud (following the adiabatic assumption), but there is some suggestion that the development of precipitation-sized droplets might lead to larger droplets being preferentially found below cloud top (Chang and Li, 2002;Nakajima et al, 2010a, 15 b; Suzuki et al, 2010) . However, Zhang et al (2012) found that MODIS retrievals of r e performed on model generated clouds were not significantly affected by the presence of precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…Platnick (2000) showed that dτ has some dependence on viewing geometry and so the consideration of a wider range of view and solar zenith angles should ideally be made. The modelling of the idealised clouds and the correction rests on the assumption that r e increases monotonically with height within the cloud (following the adiabatic assumption), but there is some suggestion that the development of precipitation-sized droplets might lead to larger droplets being preferentially found below cloud top (Chang and Li, 2002;Nakajima et al, 2010a, 15 b; Suzuki et al, 2010) . However, Zhang et al (2012) found that MODIS retrievals of r e performed on model generated clouds were not significantly affected by the presence of precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between optical depth and effective particle radius was analyzed in a similar way as in the numerical cloud simulation by Suzuki et al [6], in which the size distribution of cloud particles was simulated. Figure 3 shows an example of the comparison of the relationship between cloud with dust (left) and cloud without dust (right).…”
Section: Resultsmentioning
confidence: 99%
“…The colors of the dots indicate the BTD, indicating that the existence of dust aerosols provides negative values. According to Suzuki et al [6], cloud liquid water path increases with a constant effective radius in an unstable condition, while an increase in aerosol number concentration brings about an increase in optical depth and a decrease in effective radius. Figure 3 suggests that the number concentration of CCN saturates where the dust aerosol number concentration is sufficiently large, and the size of individual particles increases with a constant number concentration.…”
Section: Resultsmentioning
confidence: 99%
“…1b and detail in their paper). In addition to the RE-COT pattern, Nakajima et al (2010) and Suzuki et al (2010b) proposed another diagram called the Contoured Frequency Optical Depth Diagram (CFODD). Figure 1c is an example of a CFODD, which was constructed using the radar reflectivity (PR) and layered optical depth (COD, t d (z), defined as equation (3)) retrieved from active sensor on CloudSat and the RE and total cloud optical thickness (COT) of warm clouds retrieved from Aqua Moderate Resolution Imaging Spectroradiometer (MODIS) sensor.…”
Section: Introductionmentioning
confidence: 99%
“…1b) and CFODD (Fig. 1d) are described in the Suzuki et al (2010a), Suzuki (2010b), Nakajima et al (2010), and supplemental material of this paper.…”
Section: Introductionmentioning
confidence: 99%